Plurality in unity: challenges toward religious education in the Philippines - Baring, Rito V. (Religious education, 2011)
This article reviews the challenges provided by a plural condition toward doing religious education in the Philippines. The problem of Philippine religious education hinges on the fact that the growing plural condition in the educational system remains until now “un-discussed” or integrated in many schools. Not much is heard about proposing a platform of dialogue within religious education. Dialogue is more often associated with inter-faith initiatives beyond the learning environment. If religious education should be an instrument in the formation of the right Christian attitudes among the young, dialogue must be an urgent Christian agenda in Philippine religious education.